Influence of sociodemographic factors, diagnostic variations, and phenomenology toward the treatment response in adolescent catatonia in a tertiary care centre in Eastern India - Majumder, Uttam; Biswas, Parthasarathy; Biswas, Jagadish; Layek, Avik Kumar (Asian Journal of Medical Sciences, 2023)
Background: Catatonia remains an area of lesser research especially in the adolescent age group. It has subtle differences in the presentation and background diagnoses as compared to adult catatonia. There is paucity of literatures regarding the role of different sociodemographic and clinical factors attributing to different treatment response. Aims and Objectives: The aim of the study was to assess the association of socio-demographic features, background psychiatric diagnoses, and different catatonic symptoms with treatment outcome of adolescent catatonia. Materials and Methods: The study considered 10–19 years old patients admitted in the in-patient department as per diagnostic and statistical manual diagnosis. They were assessed by Pediatric Catatonia Rating Scale (PCRS) and treated with lorazepam initially with varying dosage and duration. Modified electroconvulsive therapy was administered in resistance. Factors of these two groups were statistically analyzed to assess predictability towards outcome. Results: There were 47 participants with mean age of 16.66±1.21 years of whom 29.8% showed positive family history of different psychiatric illnesses. Most of them came with schizophrenia and related disorders (53.2%), though mood disorders, conversion and organic brain diseases were also there. Among them 30 (63.8%) patients responded to lorazepam treatment. Positive family history, urban background, and catatonic severity in terms of higher PCRS score showed predictability to lorazepam non-response. Clinical features such as stupor, staring, negativism, withdrawal, mutism, urinary incontinence and refusal to eat or drink were associated with non-response, whereas waxy flexibility, stereotypy, verbigeration, and mannerism were seen in the response group. Conclusion: There is need to identify warning signs such as family history, greater symptom load and certain clinical features that can lead to resistance to the treatment with benzodiazepines based on this study. It can necessitate further large-scale study to alleviate disease burden to this young and productive population.